2015
DOI: 10.1177/1538192715607331
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Examination of Differences in College Adjustment Stressors and Depression and Anxiety Symptoms Between White, Hispanic and White, Non-Hispanic Female College Students

Abstract: Differences in four adjustment stressors (family, interpersonal, career, and academic), and depression and anxiety symptoms were examined between White, non-Hispanic and White, Hispanic undergraduate college female students. White, Hispanic female college students reported significantly greater academic and family adjustment stressors than White, non-Hispanic students. None of the socioeconomic or demographic variables predicted adjustment stress, depression, or anxiety. Findings are discussed in terms of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Undergraduate students are at an important transitional stage and may face various new challenges, such as adjustment to college life, poverty, academic pressures, part-time work, and identity changes (24)(25)(26). These stressors might increase the risk of stress-induced mental health problems in undergraduate students, such as depression (27), poor sleep quality (28,29), and suicidal ideation (30).…”
Section: Introductionmentioning
confidence: 99%
“…Undergraduate students are at an important transitional stage and may face various new challenges, such as adjustment to college life, poverty, academic pressures, part-time work, and identity changes (24)(25)(26). These stressors might increase the risk of stress-induced mental health problems in undergraduate students, such as depression (27), poor sleep quality (28,29), and suicidal ideation (30).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that as many as 27% of Latinos experience elevated depressive symptoms any given time [ 4 ], and 11% experience elevated symptoms of anxiety [ 5 ]. By comparison, 7.9% of Non-Hispanic Whites (NHW) experience elevated depressive symptoms [ 6 , 7 ], and 9% suffer from anxiety [ 8 , 9 ]. Furthermore, 14% of Latinos report a lifetime history of ataque de nervios [ 10 ], a cultural syndrome which the Diagnostic and Statistical Manual (DSM)-5 [ 11 ] classifies as a culturally-specific category of aberrant behaviors that don’t fit any other DSM disorders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a pilot study in this aspect, the current study brings new insights on the importance of a wellness course to the professional preparation of counselors-in-training and also has implications on the reconsideration of curriculum constituents of counselor education programs at the graduate level. In addition, recent research that explored college adjustment stressors, depression, and anxiety among the sample of Hispanic and White female college students has suggested that Hispanic students can benefit from help by addressing their mental health needs as they transition to college (Holliday et al, 2016). While exploring strategies that assist with adjustment stressors and improvement of mental health among college students attending predominately Hispanic institutions, it is beneficial to draw from experience of counselor preparation programs that focus on counselor wellness as of the main pillars of their preparation process.…”
Section: Statement Of the Problemmentioning
confidence: 99%